2012
DOI: 10.1007/s00125-012-2771-2
|View full text |Cite
|
Sign up to set email alerts
|

cAMP response element binding protein H mediates fenofibrate-induced suppression of hepatic lipogenesis

Abstract: Aims/hypothesis Fenofibrate is a drug used to treat hyperlipidaemia that works by inhibiting hepatic triacylglycerol synthesis. Sterol regulatory element binding protein-1c (SREBP-1c) is a major regulator of the expression of genes involved in hepatic triacylglycerol synthesis. In addition, endoplasmic reticulum (ER)-bound transcription factor families are involved in the control of various metabolic pathways. Here, we show a novel function for an ER-bound transcription factor, cAMP response element binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
2
15
1
Order By: Relevance
“…Certainly, adenoviral overexpression of pCREB3L3 in the livers of Ldlr -/- Creb3l3 -/- mice reduced nSREBP-1 and nSEEBP-2 protein expression (Figure 6B), indicating that in Ldlr -/- mice, SREBP cleavage was regulated by existence of pCREB3L3, rather than Insigs. It was reported that CREB3L3 suppresses LXRα-induced Srebf-1c expression by inhibiting LXRα binding to Srebf-1c promoter ( Min et al, 2013 ); however, in our data settings, Ldlr -/- TgCREB3L3 mice exhibited no changes in Srebf1c and its target genes.…”
Section: Discussioncontrasting
confidence: 86%
“…Certainly, adenoviral overexpression of pCREB3L3 in the livers of Ldlr -/- Creb3l3 -/- mice reduced nSREBP-1 and nSEEBP-2 protein expression (Figure 6B), indicating that in Ldlr -/- mice, SREBP cleavage was regulated by existence of pCREB3L3, rather than Insigs. It was reported that CREB3L3 suppresses LXRα-induced Srebf-1c expression by inhibiting LXRα binding to Srebf-1c promoter ( Min et al, 2013 ); however, in our data settings, Ldlr -/- TgCREB3L3 mice exhibited no changes in Srebf1c and its target genes.…”
Section: Discussioncontrasting
confidence: 86%
“…Increased ATGL and CPT I expression levels induced by fenofibrate have been reported in several studies [25][26][27]. Studies also indicated that fenofibrate induced mRNA expression of the enzymes involved in fatty acid oxidation in a variety of species [28,29]. ATGL is a rate-limiting lipolytic enzyme, which initiates hydrolysis of triglyceride and produces diacylglycerol and fatty acids [30].…”
Section: Discussionmentioning
confidence: 92%
“…Total TG levels in liver were analyzed using Infinity reagents (Thermo DMA, Louisville, CO, USA), according to the manufacturer's protocol, as mentioned previously [21,22]. Serum TG levels were measured using a commercially available determination kits (Sigma-Aldrich).…”
Section: Measurement Of Hepatic and Serum Tg Contentsmentioning
confidence: 99%
“…For hematoxylin and eosin (H & E) staining, liver tissue samples were fixed with 4% paraformaldehyde and embedded with paraffin, as described previously [21,22]. Liver sections (4-5 μm) were performed with H & E staining according to the standard procedures.…”
Section: Histological Analysismentioning
confidence: 99%